Morphological assessment of dentine and cementum following apicectomy with Zekrya burs and Er:YAG laser associated with direct and indirect Nd:YAG laser irradiation - Maranhao de Moura, Abilio Albuquerque [UNESP]; Moura-Netto, Cacio [UNESP]; Barletta, Fernando Branco; Vieira-Junior, Nilson Dias; Eduardo, Carlos de Paula (Mosby-elsevier, 2010)
Objectives. This study aimed to assess the apical surface morphology of maxillary central incisors resected 3.0 mm from the tooth apex using Zekrya burs or Er:YAG laser, with or without subsequent direct Nd:YAG laser irradiation (apical and buccal surfaces) and indirect irradiation (palatal surface).Study design. Forty maxillary central incisors were instrumented and obturated. The roots were divided into 4 groups according to the root resection method (Zekrya bur or Er: YAG laser -1.8 W, 450 mJ, 4 Hz, 113 J/cm(2)) and further surface treatment (none or Nd: YAG laser -2.0 W, 100 mJ, 20 Hz, 124 J/cm(2)). The teeth were prepared for SEM analysis. Scores ranging from 1 to 4 were attributed to cut quality and morphological changes. The data were analyzed by the Kruskal-Wallis test and by Dunn's test.Results. SEM images showed irregular surfaces on the apical portions resected with Zekrya burs, with smear layer and grooves in the resected dentine and slight gutta-percha displacement and plasticization. on the other hand, apicectomies carried out with Er: YAG laser showed morphological changes compatible with ablated dentine, with rough surfaces and craters. In spite of the presence of plasticized gutta-percha, with the presence of bubbles, an irregular adaptation of the filling material to the root walls was also observed. Direct Nd: YAG laser irradiation of the apical and buccal surfaces of the resected roots resulted in areas of resolidification and fusion in the dentine and cementum, with a vitrified aspect; indirect Nd: YAG laser irradiation of the palatal surfaces yielded a lower number of changes in the cementum, with irregular resolidification areas.Conclusions. There were no differences in terms of cut quality between the use of burs and Er: YAG laser or between the 2 surfaces (apical and buccal) treated with Nd: YAG laser with direct irradiation. However, morphological changes were significantly less frequent on surfaces submitted to indirect irradiation (palatal) when compared with those directly irradiated. (Oral Surg Oral Med Oral Pathol Oral Radiol Endod 2010; 109: e77-e82)